IMPLEMENTATION OF THE PANCASILA AND RAHMATAN LIL 'ALAMIN STUDENT PROFILE STRENGTHENING PROJECT AT MAN WEST LOMBOK - Muhammad Ihsanul Amali (Sinar Lima, 2025)
This research was motivated by the author's attention to studying the profile of Pancasila students. Because the rapid development of the times makes challenges in education begin to emerge. The purpose of this research is to find out the implementation of the project to strengthen the profile of Pancasila students at MAN West Lombok. The type of research used in this research is qualitative research, which is research that describes the data as it is in accordance with field conditions. The data collection techniques in this study used observation, interviews and documentation techniques. Data analysis used reduction, presentation and verification. From the results of data collection, the results show that: the learning process of the Pancasila Student Profile Strengthening Project at West Lombok Man is carried out through the process of preparation, implementation and evaluation. In the implementation of the Pancasila Student Profile Strengthening Project at MAN West Lombok, The theme used is